The correlation of folic acid and homocysteine serum with vascular density and retinal non-perfusion area in diabetic retinopathy - Andhika Guna Dharma; Arief Wildan; Maharani Maharani; Riski Prihatningtias; Fifin Luthfia Rahmi; Trilaksana Nugroho; Arnila Novitasari Saubig; Zahira Rikiandraswida (Indonesian Nutrition Association, 2024)
Background : Diabetic Retinopathy (DR) is the most common microvascular complication of Diabetes Mellitus (DM). Homocysteine has been studied as a biomarker in DR, while folic acid exhibits anti-proliferative effects in DR. Objective : To analyze the correlation between folic acid and homocysteine serum with vascular density and retinal non-perfusion area in healthy individuals and patients with diabetic retinopathy. Methods : This is an observational study with a cross-sectional design, conducted in Dr. Kariadi Hospital and GAKI laboratory in Semarang in January 2023. This study included 60 samples: 15 healthy individuals, 15 patients with DM but no DR, 15 patients with Non-Proliferative Diabetic Retinopathy (NPDR), and 15 patients with Proliferative Diabetic Retinopathy (PDR). Patients were examined for serum folic acid and homocysteine using blood laboratory tests, vessel density and retinal non-perfusion areas using optical coherence tomography angiography (OCTA). Results : There was a negative correlation with weak strength between folic acid levels and retinal non-perfusion area of the retina in all samples (Folic acid levels vs retinal non-perfusion area, p = 0.009, Spearman correlation = -0.335). There was a positive correlation with weak strength between folic acid levels and vascular density in all samples (Folic acid levels vs vascular density, p = 0.009, Spearman correlation = 0.337). There was a positive correlation with moderate strength between homocysteine levels and retinal non-perfusion area in all samples (Homocysteine levels vs non–perfusion area of the retina, p = 0.001, Spearman correlation = 0.426). There was a positive correlation with moderate strength between homocysteine levels and vascular density in all samples (Homocysteine levels vs vascular density, p = 0.001, Spearman correlation = -0.414). Conclusion : There was a correlation between folic acid and homocysteine serum with vascular density and retinal non-perfusion areas.